Study of Drug-Drug Interactions in General Medicine Department of a Tertiary Care Hospital - Kousalya Kaliamurthy, Anil Kumar, Saranya Punniyakotti, Praveen Devanandan (Journal of Applied Pharmaceutical Science, 2015)
Objectives Drug therapy (DT) is growing more complex, thus appropriate drug prescription becomes increasingly challenging. Drug interactions (DI) are one of the important factors that modify the response to a drug. The main objective of this study was to monitor the potentially serious and significant Drug-Drug Interactions (DDIs). Material and methods The number of drugs prescribed for each patient, drugs taken by the patient and the drug interactions were recorded. The interactions between the drugs were assessed using Micromedex software and Stockley’s Drug Interaction. The type and severity of prescription with DDIs was also assessed. Results The number of potential DDIs for the study population was 390 and each prescription had at least one interaction. Of the total potential DDIs (n=390) identified, majority were of moderate severity (n = 257, 65.90%). Most frequent DDI was seen between Metformin + Ranitidine (moderate interaction) in 70 prescriptions (50%) and between Ranitidine + Acetaminophen (minor interaction) in 48 prescriptions (34.29%). The common major interactions were seen between Rabeprazole + Clopidogrel in 4 prescriptions (2.86%), Enalapril + Spironolactone and Ciprofloxacin + Tramadol in 3 prescriptions (2.14%). Conclusion The drug related problems, primarily the drug interactions is a permanent patient related risk in hospitals and the utilization of computer software has become the best way to identify and prevent them.
Keywords: Drug-Drug Interactions, Drug Related Problems, Adverse Events.